MALIN KUNDANG, IBUNYA DURHAKA: Suatu Pendekatan Genetik - Ronidin, Ronidin (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2011)
This paper discuss the influence ofÂ  kaba â€œMalin Kundang" as a form of oral literature of the short story parody Minangkabau A.A. Navis entitled "Malin Kundang, Ibunya Durhaka" (â€œMKIDâ€). The discussion carried out by using a genetic approach. Genetic approach examines how the work affects the work of others. Analysis conducted â€œMKIDâ€Â  illustrates that the short story as a parody of the affected works of kaba "Malin Kundang" indicates a social critique of Navis toward modern societyâ€”especially the people within the scope of the author, the Minangkabau peopleâ€”whom have been uprooted from its cultural roots, so that in everyday life they become materialistic and overturning of moral values and religion. In pursuit of his passion, they perform a variety of "sedition" is sometimes hard to accept common sense. World upside down in a short story in which a â€œMKIDâ€ mother "disobey" her and "cheating" for his worldly needs, is a portrait of a sick society, unstable, and turned upside down. Key words:Â  Malin Kundang, son, mother, sedition, influence, parody